Taking Offence - Vogel, Carl (My University, 2020)
Between speakers and addressees, the perception of offensiveness in natural language may diverge distinctly to the potential for divergence of understanding of lexical content. Historically, the perception of offensiveness would be treated as a matter of pragmatics rather than semantics. Here, the semantic nature of offence, in particular, taking offence, even where none was intended, is addressed. A formal account is provided, with semantic composition rules corresponding to interpreter personality types.
{11th IEEE International Conference on Cognitive Infocommunications (CogInfoCom2020)
Keywords: Digital Engagement; Digital Humanities; Computational Linguistics; Computational linguistics; DYNAMIC SEMANTICS; Formal Semantics; Pragmatics; SEMANTICS; Semantics; computational linguistics; impoliteness; politeness; syntax-pragmatics interface